Amyloid in bone marrow smears in systemic light-chain amyloidosis. (2nd January 2017) - Kimmich, Christoph; Schönland, Stefan; Kräker, Sandra; Andrulis, Mindaugas; Ho, Anthony D.; Mayer, Gudrun; Dittrich, Tobias; Hundemer, Michael; Hegenbart, Ute
Abstract: We performed a prospective sensitivity analysis to detect amyloid in bone marrow (BM) smears stained with Congo red (CR) and according to Pappenheim of patients with systemic light-chain (AL) amyloidosis. Results were directly compared to routine BM histology and fat aspiration. We analysed 198 BM smears from patients with the diagnosis or suspicion of systemic AL amyloidosis. Ultimately, the diagnosis could be established for 168 patients. Amyloid was detected on BM smears with CR in 33% (56/168). All patients suspicious for amyloid on Pappenheim staining ( n = 39) showed substantial amyloid infiltration on CR. No patient without systemic AL amyloidosis stained positive. Sensitivity for routine BM histology was 57% (74/129) and for fat aspiration 96% (134/140). Patients with amyloid on BM smears had significantly more hepatic (42 vs. 9%, p < .001), renal (78 vs. 43%, p < .001) and gastrointestinal involvement (40 vs. 22%, p < .01) and less commonly cardiac involvement (58 vs. 76%, p < .03) and consecutively no adverse prognosis. CR staining of BM smears cannot be recommended as a primary screening tool for systemic AL as its overall sensitivity is far inferior to BM histology and fat aspiration. However, we recommend using the technique when suspecting amyloid on Pappenheim staining to establish the diagnosis of systemic AL amyloidosis.